2021
DOI: 10.1088/2058-9565/abdca3
|View full text |Cite
|
Sign up to set email alerts
|

CeNTREX: a new search for time-reversal symmetry violation in the 205Tl nucleus

Abstract: The Cold molecule Nuclear Time-Reversal EXperiment (CeNTREX) is a new effort aiming for a significant increase in sensitivity over the best present upper bounds on the strength of hadronic time reversal (T ) violating fundamental interactions. The experimental signature will be shifts in nuclear magnetic resonance frequencies of 205 Tl in electrically-polarized thallium fluoride (TlF) molecules. Here we describe the motivation for studying these T -violating interactions and for using TlF to do so. To achieve … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 79 publications
0
36
0
Order By: Relevance
“…It is interesting to contrast AlF to the case of TlF, where recently it was shown that unresolved hyperfine structure in the ground state significantly limits the optical cycling rate [40]. Here, the hyperfine structure in the excited state is about 30 times larger than in AlF and the natural linewidth of the optical cycling transition is about 50 times narrower.…”
Section: Hyperfine Levelsmentioning
confidence: 95%

Optical cycling of AlF molecules

Hofsäss,
Doppelbauer,
Wright
et al. 2021
Preprint
“…It is interesting to contrast AlF to the case of TlF, where recently it was shown that unresolved hyperfine structure in the ground state significantly limits the optical cycling rate [40]. Here, the hyperfine structure in the excited state is about 30 times larger than in AlF and the natural linewidth of the optical cycling transition is about 50 times narrower.…”
Section: Hyperfine Levelsmentioning
confidence: 95%

Optical cycling of AlF molecules

Hofsäss,
Doppelbauer,
Wright
et al. 2021
Preprint
“…Searches for EDMs of diamagnetic atoms in other systems have been carried out [50][51][52][53][54]; many of these are ongoing efforts with the prospect of improving measurement accuracy by orders of magnitude, such as the radium EDM search in which several upgrades are in the process of being implemented [55,56]. There are also a number of new experiments that have the potential to explore unconstrained parameter space for symmetry violating effects in the nuclear sector [45,[57][58][59][60][61][62][63], such as the CENTREX experiment that employs a cold beam of TlF molecules [64], a search particularly sensitive to the proton EDM [65,66].…”
Section: Searches For Parity-and Time-reversal-violating Electric Dip...mentioning
confidence: 99%
“…8,18,21,22 The most stringent limit on an NSM results from measurements involving 199 Hg 23 . Several other NSM experiments in other atomic [24][25][26][27] and molecular 28,29 systems are also underway. The best bounds on a NMQM are obtained from (2) measurements of atomic Cs 30 .…”
Section: Introductionmentioning
confidence: 99%